Determination of Salt Tolerance Levels of Some Radish Cultivars and Evaluation of the Effectiveness of Salicylic Acid on Germination in Saline Conditions - Ulukapı, Kamile; Nasırcılar, Ayşe Gül; Kurt, Zehra (Turkish Journal of Agriculture - Food Science and Technology, 2020)
This study was conducted to determine tolerance levels of different radish varieties (white, black, red, little red radish) under salt stress conditions and to evaluate the effectiveness of exogenous salicylic acid (SA) application on germination and vegetative development. For this purpose; germination percentage (%), germination time (day), germination index calculated, and then number of leaves, shoot length (cm), root length (cm), leaf width (cm), leaf length (cm), stem diameter (mm), plant fresh and dry weights (g) were measured. Radish seeds were germinated at control, 100 mM, 150 mM and 200 mM salt concentrations. Salt stress did not inhibit germination at a high level but negatively affected the vegetative growth of plants. According to the results of the statistical analysis of the data obtained, 150 mM was determined as the threshold value. Then, SA was applied to seeds treated with 150 mM salt concentration at different doses (0.25, 0.50, 0.75, 1.00 mM). SA had a positive effect on germination in saline conditions in general and it was concluded that 0.50 mM SA could be applied for germination percentages in all cultivars. However, 1 mM SA inhibited the germination of big red and little red radish cultivars, causing sudden and severe germination losses (10%, 8%, respectively). The effects of SA on vegetative growth parameters differed by cultivar and it was found to be inhibitory in terms of vegetative growth characteristics of white radish cultivar. On the other hand, 0.50 mM SA in black and big red, 0.75 mM SA in little red cultivar gave promoting results for vegetative growth.